Populism and heritage in Europe - Kaya, Ayhan, author.
1 online resource.
Keywords: "Populism and Heritage in Europe explores popular discourses about European and national heritage that are being used by specific political actors to advance their agendas and to prevent minority groups from being accepted into European society. Investigating what kind of effect the politics of fear has on these notions of heritage and identity, the book also examines what kind of impact recent events and crises have had on the types of European memories and identities that have been promoted by the supporters of right-wing populist parties. Based on qualitative fieldwork conducted in six countries, this book specifically analyses how anti-European identities are being articulated by right-wing populist individuals. Providing an analysis of the manifestos, speeches and official documents of such parties, the book examines how they instrumentalise xenophobia, Islamophobia, Euroscepticism, globalisation and international trade in European spaces to mobilise the masses hit by financial crisis and refugee crisis. Drawing on in-depth interviews with the sympathisers of populist movements, Kaya provides some insights into the main motivations of these individuals in resorting to nativist and populist discourses, whilst also providing a thorough analysis of the use of the past and heritage by such parties and their followers. Populism and Heritage provides a unique insight into one of the most contested trends of the contemporary age. As such, the book should be of great interest to those working in the fields of heritage studies, cultural studies, politics, sociology, anthropology, philosophy and history"--